Akselerasi peningkatan literasi Al Quran berbasis internet Studi Kasus : Implementasi Program Pelatihan Penerjemahan Al Quran Metode Al Huda pada masyarakat - Chairullah Harun (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
Increasing Al-Quran literacy means improving the ability to "read" the Arabic script of Al-Quran and the ability to "translate" it into Indonesian. Research results from the Jakarta Al-Quran Science Institute in 2022 show that 72% of Indonesian Muslims are unable to read Al-Quran. The main reasons are because the majority of Indonesian Muslims do not speak Arabic. This "Al-Quran emergency" condition will cause Indonesian Muslims to be easily swayed by their religious beliefs and knowledge, their faith is fragile and their religious insight is narrow. The Al Huda method is a method of translating Al-Qur'an that utilizes advances in information technology, aimed at those who wish to be able to translate Al-Quran themselves (independently). This research aims to evaluate the implementation of the Al Huda method in translating Al-Quran. The research population were group of Al Huda method training students, both offline and online groups. By using a qualitative approach and applying analytical-descriptive methods, the research results concluded that as long as the students participating in the training already had the "ability to read Al-Quran" well and fluently, the Al Huda method was successful in helping students translate Al-Quran themselves easily.